HIGHER ORDER THINKING SKILLS AMONG ENGLISH TEACHERS ACROSS GENERATION IN EFL CLASSROOM - Mursyid Mursyid; Nia Kurniawati (University of Kuningan, 2019)
Higher order thinking skills are the next cognitive ability to evaluate, analyze and create. It is a must for English teachers across generation (Baby Boomers, Generation X, and Generation Y) to grasp and implement the idea of HOTS in their classrooms. Teaching English in EFL setting certainly forces the teachers to have expertise in planning the learning activities that would foster students’ thinking skills, especially their HOTS. This study aims at investigating the perceptions, the practice, and the constraints in endorsing higher order thinking skills in teaching foreign language. This case study involved seven senior high school English teachers from three generations (Baby Boomers, generation X, and generation Y). Data were collected through open-ended questionnaire, classroom observation, and document analysis for triangulation purpose. Data were then categorized and classified to form themes for the study. The results showed that teachers from all generation are aware of HOTS and they are applying it in their teaching in a different way. However, some obstacles are still found in incorporating HOTS in their classroom.